Ants of the State of Pará, Brazil: a historical and comprehensive dataset of a key biodiversity hotspot in the Amazon Basin - de Albuquerque, Emília Zoppas; Prado, Lívia Pires Do; Andrade-Silva, Joudellys; de Siqueira, Emely Laiara Silva; Da Silva Sampaio, Kelly Liane; Alves, Diego; Brandão, Carlos Roberto Ferreira; Andrade, Paloma L.; Feitosa, Rodrigo Machado; de Azevedo Koch, Elmo Borges; Delabie, Jacques Hubert Charles; Fernandes, Itanna; et al. (Zootaxa, 2021)
The state of Pará in northern Brazil is located entirely within the Amazon Basin and harbors a great diversity of landscape and vegetation types that support high levels of biodiversity. Here, we provide a comprehensive inventory of ant species and their distribution in Pará. This regional list is based on an extensive review of species records from published and unpublished sources covering a period of 134 years (1886–2020) and includes the five most representative ant collections in Brazil. In total, we documented 12 subfamilies, 90 genera and 753 ant species, including 97 species recorded for the first time in Pará and 12 species newly reported in Brazil. Sampling effort across the state is highly uneven, and most records may be associated with research areas near the state capital, mining areas, hydroelectric dams, and research field stations run by the state or universities. In addition, our results suggest a strong bias in ant collection in Pará in terms of proximity of sampled sites to access routes, such as roads and rivers. We also found that species records were highly unevenly distributed based on areas of endemism within the Amazon, vegetation type, and protected areas within the state. Ant surveys are still lacking from most protected areas of Pará, and further sampling is urgently needed in view of the current trend of expansion of major infrastructure projects and natural resource harvesting within protected areas of Pará. Our database represents an extremely valuable and rich source of information for further studies on ant biodiversity and conservation in the Amazon Basin.